Product architecture and product market internationalization: A conceptualization and extension. (7th January 2020) - Burton, Nicholas; Nyuur, Richard; Amankwah‐Amoah, Joseph; Sarpong, David; O'Regan, Nicholas
Abstract: Designing a modular product architecture and corresponding organization design may enable firms to internationalize more effectively and efficiently. Open and closed, integrated, and modular product architectures may be associated with increasing product market and firm internationalization. We postulate that the more open and modular the product architecture, the easier product market internationalization becomes. We hypothesize that an open and modular product architecture may permit international product markets to become "components" within a strategy of "modular internationalization."